Musical Composition of Gender Wayang "Silat Lidah" | Komposisi Musik Gender Wayang "Silat Lidah" - Ni Putu Hartini (GHURNITA: Jurnal Seni Karawitan, 2021)
Silat Lidah is a musical composition that uses the Instrument of Gender Wayang as a medium for expressing interesting musicals such as melody, rhythm, timbre (sound color), tempo, and dynamics. The meaning of Silat Lidah is to harmonize the family who are debating. The shape or structure of this music uses intermittent musical sentences in tempo and dynamics for different in perception in family conflicts. The concept of the Silat Lidah is divided into three parts, from the three sections producing different characters for approval of the Silat Lidah. The Karawitan artwork with the title Silat Lidah is displayed in Pura Dalem, Desa Adat Munggu, which is supported by 4 musicians or performers including composer who participate in the presentation. The selected musician or performer is a player who has expertise in Gender Wayang musics consisting of two players of Gender Wayang Pemade and two players of Gender Wayang Kantilan.